Optogenetic manipulation of cyclic guanosine monophosphate to probe phosphodiesterase activities in megakaryocytes - Yujing Zhang; Pascal Benz; Daniel Stehle; Shang Yang; Hendrikje Kurz; Susanne Feil; Georg Nagel; Robert Feil; Shiqiang Gao; Markus Bender (Open Biology, 2022)
Cyclic guanosine monophosphate (cGMP) signalling plays a fundamental role in many cell types, including platelets. cGMP has been implicated in platelet formation, but mechanistic detail about its spatio-temporal regulation in megakaryocytes (MKs) is lacking. Optogenetics is a technique which allows spatio-temporal manipulation of molecular events in living cells or organisms. We took advantage of this method and expressed a photo-activated guanylyl cyclase, Blastocladiella emersonii Cyclase opsin (BeCyclop), after viral-mediated gene transfer in bone marrow (BM)-derived MKs to precisely light-modulate cGMP levels. BeCyclop-MKs showed a significantly increased cGMP concentration after illumination, which was strongly dependent on phosphodiesterase (PDE) 5 activity. This finding was corroborated by real-time imaging of cGMP signals which revealed that pharmacological PDE5 inhibition also potentiated nitric oxide-triggered cGMP generation in BM MKs. In summary, we established for the first-time optogenetics in primary MKs and show that PDE5 is the predominant PDE regulating cGMP levels in MKs. These findings also demonstrate that optogenetics allows for the precise manipulation of MK biology.